Atmospheric methane and carbon dioxide concentrations measured during ALKOR cruise AL561 on 2021-08-04 - Tim Weiß; Mark Schmidt (PANGAEA, 2025)
Atmospheric gas concentrations of CH4 and CO2 were measured with Picarro G2301-f analyser during AL561 cruise onboard RV Alkor (02.-12.08.2021). The gas inlet was placed at the bow of RV Alkor, at 6 m above sea level, to identify natural and anthropogenic methane anomalies near the sea surface (Schmidt et al., 2021). Concentration data are correlated with GPS-position and weather data (DSHIP) using time stamps (UTC); calculated in 1-3s averages.
In: Weiß, T; Schmidt, M (2025): Time series of atmospheric methane and carbon dioxide concentrations measured during ALKOR cruise AL561 in 2021 (Skagerrak) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.982676